Perlindungan Hukum Terhadap Tenaga Kerja Wanita (Studi di Kabupaten Magetan) - Tatik Mulyati (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2019)
Protection of Indonesian workers abroad is an integral part of protecting citizens as a state obligation. Nonetheless, the government still does not provide maximum protection to migrant workers who work abroad, especially those who experience torture and violence. This study aims to look at the juridical study of the protection of the rights of woman migrant workers abroad. This study is a literature study that is qualitative descriptive. Data collection through documentation. Meanwhile, the data analysis technique used is content analysis. The results of the study show that the existence of several laws and regulations such as Undang-Undang No.18 Year 2017 concerning the Protection of Indonesian Migrant Workers along with their derivative rules is a juridical basis for woman workers who work abroad have provided a legal protection for Indonesian workers abroad.